2001
DOI: 10.1002/1438-9312(200111)103:11<752::aid-ejlt752>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of edible oils with natural antioxidants

Abstract: Natural antioxidants have recently gained increased interest because of the belief that natural food ingredients are better and safer than synthetic ones. The review presents the results on stabilisation of the main edible oils with different types of natural antioxidants. Sources of natural antioxidants are spices, herbs, teas, oils, seeds, cereals, cocoa shell, grains, fruits, vegetables, enzymes, proteins. Researchers concentrate on ascorbic acid, tocopherols and carotenoids as well as on plant extracts con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(146 citation statements)
references
References 114 publications
2
128
0
10
Order By: Relevance
“…Certain compounds including carbonyl compounds, aldehydes, acids, ketones, epoxides and carbon-di-oxide cause rancid taste and smell during the oxidation of unsaturated fats (Sarkardei & Howell, 2007;Singh, Marimuthu, Murali, & Bawa, 2005;Yanishlieva & Marinova, 2001;Yu, Scanlin, Wilson, & Schmidt, 2002). Synthetic (Dragoev, 2008;Huang & Weng, 1998;Khalil & Mansour, 1998;Ohshima, Yankah, Ushio, & Kiozumi, 1998) and natural antioxidants (Ramanathan & Das, 1992;Tang, Sheehan, Buckley, Morrissey, & Kerry, 2001;Xin & Shun, 1993) are the most common treatment methods to prevent or delay the lipid oxidation in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Certain compounds including carbonyl compounds, aldehydes, acids, ketones, epoxides and carbon-di-oxide cause rancid taste and smell during the oxidation of unsaturated fats (Sarkardei & Howell, 2007;Singh, Marimuthu, Murali, & Bawa, 2005;Yanishlieva & Marinova, 2001;Yu, Scanlin, Wilson, & Schmidt, 2002). Synthetic (Dragoev, 2008;Huang & Weng, 1998;Khalil & Mansour, 1998;Ohshima, Yankah, Ushio, & Kiozumi, 1998) and natural antioxidants (Ramanathan & Das, 1992;Tang, Sheehan, Buckley, Morrissey, & Kerry, 2001;Xin & Shun, 1993) are the most common treatment methods to prevent or delay the lipid oxidation in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Spices and herbs, generally, used in food stuffs for enhancing the flavor or color attributes, have antimicrobial as well as antioxidant activity (Baydar et al, 2004;Sa≈dic and Ȏ zcan 2003;Yanishlieva and Marinova, 2001). It has been reported that dried herbs and essential oils have been successfully used to reduce lipid oxidation in meat products (Estevez and Cava, 2006).…”
mentioning
confidence: 99%
“…It has been reported that dried herbs and essential oils have been successfully used to reduce lipid oxidation in meat products (Estevez and Cava, 2006). Natural antioxidants have been reported to be more powerful than the synthetic antioxidants especially rosemary, sage and green tea extracts (Tang et al, 2001;Wanasundara and Shahidi, 1998;Yanishlieva and Marinova, 2001;Zandi and Gondon, 1999). Sage (Salvia Officinalis) is a popular Labiatae herb with a verified potent antioxidant activity.…”
mentioning
confidence: 99%
“…As Japanese quince seed oil and seed extracts contain natural antioxidants (various polyphenols), the oil could be used for stabilisation of other oils -similar examples of application of other plant seeds have been described (Yanishlieva and Marinova, 2001;Poiana, 2012;Rubilar et al, 2012); stabilisation by linseed oil has been studied more often (Omar et al, 2010;Michotte et al, 2011).…”
Section: Discussionmentioning
confidence: 99%